(untitled) (Research, Society and Development, 2021)
Urban trees positively influence the quality of life in cities, but they need to be pruned regularly, generating a large amount of solid urban waste. This study aimed to compost urban pruning waste, evaluate its physical, chemical, structural characteristics, and determine its potential as a substrate to produce forest seedlings. The pruning residue was obtained from the Rio de Janeiro Municipal Cleaning Company (COMLURB) - Brazil. Twigs and leaves ≤ 8 cm in diameter were chopped and arranged on a trapezoidal windrow. Temperature, humidity, and aeration were controlled throughout the composting process. Irrigation and turning were carried out as needed. The composting process took 122 days. The compost was dried, processed, and evaluated for physical and chemical characteristics. The leachate was collected and characterized by 13C CP MAS NMR. The temperature patterns were consistent with the thermophilic, mesophilic, and maturation stages. Part of the chemical and physical characteristics of the compound was classified as adequate, according to the literature. The leachate contained large amounts of C alkyl and low amounts of C carbonyl at all times of composting. The characteristics determined indicated that the composting process was interrupted before complete maturation was achieved. However, the compound can be combined with other materials to produce a complete substrate.